Electric Vehicle Adoption: A Tpb-Based Conceptual Framework With Esg and Policy Insights From Slovakia - Khalilov, Ismayil (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper develops a theory-driven conceptual framework based on the Theory of Planned Behaviour (TPB) to explain individual consumer adoption of electric vehicles (EVs) within the context of sustainability, ESG considerations, and public policy. Drawing on a structured review of high-quality academic literature, the study examines how attitudes, subjective norms, and perceived behavioural control influence EV adoption decisions, with particular emphasis on environmental and sustainability-related factors. The paper does not present original empirical data; instead, it proposes an extended TPB-based model tailored to EV adoption, integrating psychological, economic, infrastructural, and ESG-related dimensions. In addition, policy-relevant factors–such as financial incentives, regulatory support, and charging infrastructure–are incorporated to reflect their role in shaping consumer perceptions and behavioural control. To enhance practical applicability, the framework is operationalised through the development of measurement items for each construct, providing a foundation for future empirical research. The Slovak market is used as a contextual reference to illustrate the relevance of policy and market-specific conditions. The study contributes by linking consumer behaviour theory with ESG and policy perspectives, offering an integrated and operationalizable framework to better understand and support the transition toward sustainable mobility.